Development of an efficient diagonally implicit Runge–Kutta–Nyström 5(4) pair for special second order IVPs - Ahmed Demba, Musa; Senu, Norazak; Ramos, Higinio; Watthayu, Wiboonsak (MDPI, 2022)
In this work, a new pair of diagonally implicit Runge–Kutta–Nyström methods with four stages is constructed. The proposed method has been derived to solve initial value problems of special second-order ordinary-differential equations. The principal local truncation error of the new method is obtained, and the main characteristics of the new method are analyzed. Some numerical experiments are performed, which demonstrate the robustness and efficiency of the new embedded pair.